Clinical presentation of craniopharyngiomas in pediatric age group: retrospective analysis of 24 cases - Asan, Ziya; Dashti, Reza; Erdinçler, Pamir; Özlen, Fatma; Çıplak, Nejat (Cerrahpaşa Medical Journal, 2013)
Objectives: In this study clinical presentation and laboratory findings of 24 pediatric craniopharyngioma patients (age 5-15) admitted to Istanbul University Department of Neurosurgery between 1998-2008 were retrospectively evaluated and compared with current literature Methods: Clinical data of 24 patients were retrospectively evaluated. Age,sex, clinical presentation and laboratory findings were recorded for evaluation. Results: The main presenting symptoms of 24 patients were as follows: headache in 10 patients (%42); visual problems in 18 patients (75%), endocrine abnormalities in 7 patients (29%); nausea and vomiting in 2 patients (8%), seizures in 1 patient (4%); and motor deficits in 2 patients (8%). Conclusion: Comparing our results to current studies it shows that; clinical presentation of craniopharyngiomas in pediatric age group can be highly variable. Apart from routine radiological work up detailed endocrine and ophthalmologic studies are mandatory.